2015
DOI: 10.1590/s0036-46652015000600003
|View full text |Cite
|
Sign up to set email alerts
|

MOLLUSCICIDAL AND LARVICIDAL ACTIVITIES OF Atriplex inflata AERIAL PARTS AGAINST THE MOLLUSK Galba truncatula, INTERMEDIATE HOST OF Fasciola hepatica

Abstract: Fasciolosis is a widespread parasitosis of farm live-stock in many developing countries. For this reason, it is necessary to search for new substances against parasitic diseases caused by flukes. Indeed, a wide variety of terrestrial plants have been subjected to chemical and pharmacological screening in order to discover their potential for human medicinal use. The molluscicidal and larvicidal activities of Atriplex inflata were tested on Galba truncatula and Fasciola hepatica larval stages infecting this sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…There are papers using Becker with a maximal volume of 250 mL containing 10 mollusks for treatment [ 13 , 16 , 17 ], 500 mL with 10 mollusks [ 8 , 18 , 19 ], 1000 mL with 10 mollusks [ 20 , 21 ], and in rare cases 2000 mL [ 22 ]. However, these papers, changing the final volume and number of mollusks, did not validate mathematically the efficiency of these protocols to measure molluscicidal activity in comparison to standard protocol.…”
Section: Discussionmentioning
confidence: 99%
“…There are papers using Becker with a maximal volume of 250 mL containing 10 mollusks for treatment [ 13 , 16 , 17 ], 500 mL with 10 mollusks [ 8 , 18 , 19 ], 1000 mL with 10 mollusks [ 20 , 21 ], and in rare cases 2000 mL [ 22 ]. However, these papers, changing the final volume and number of mollusks, did not validate mathematically the efficiency of these protocols to measure molluscicidal activity in comparison to standard protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products, such as glycosides extracted from fresh leaves of Nerium indicum (DAI et al, 2011) and fractions of the methanolic extract of seed flour Camellia oleifera (KIJPRAYOON et al, 2014), also caused P. canaliculata mortality. Molluscicidal effect of the EO Cymbopogon winterianus against Biomphalaria glabrata (RODRIGUES et al, 2013) and the hexane and ethyl acetate extracts from the aerial parts of Atriplex inflata against Galba truncatula (HAMED et al, 2015) have also been described.…”
Section: Bianchini Et Almentioning
confidence: 99%
“…Products extracted from plants are promising alternatives because they are biodegradable and from renewable sources; they also have fewer adverse effects on the ecosystem. There are studies reporting molluscicidal activity of some plant extracts against P. canaliculata (DAI et al, 2011;KIJPRAYOON et al, 2014) and other mollusk species (RODRIGUES et al, 2013;HAMED et al, 2015). In this context, the aim of this study was to evaluate possible molluscicidal and/or relaxing effects of eugenol and the EOs of Origanum majorana, Ocimum americanum, Hesperozygis ringens, and Piper gaudichaudianum on P. canaliculata.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, triterpenoids isolated from A. laciniata demonstrated antibacterial, antioxidant and antiurease activities ( 15 ), including anticholinesterase effects against Alzheimer's and other neurological disorders ( 16 ). The fungicidal effects of A. semibaccata, A. portulacoides and A. infalata have been previously reported ( 17 ) and the molluscicidal and larvicidal activities of A. inflata have also been identified ( 18 ). Furthermore, Gođevac et al ( 19 ) revealed that flavonoid glycosides isolated from the aerial parts of A. littoralis exhibited protection against in vitro biochemical and cytogenetic damage to human lymphocytes ( 19 ).…”
Section: Introductionmentioning
confidence: 96%